RETRACTED ARTICLE: MiR-29a-5p inhibits proliferation and invasion and induces apoptosis in endometrial carcinoma via targeting TPX2. Issue 10 (19th May 2018) - Jiang, Tiechao; Sui, Dongming; You, Dong; Yao, Songmei; Zhang, Lirong; Wang, Yingjian; Zhao, Jixue; Zhang, Yaozhong
Statement of Retraction: We, the Editors and Publisher of the journal Cell Cycle, have retracted the following article: Tiechao Jiang, Dongming Sui, Dong You, Songmei Yao, Lirong Zhang, Yingjian Wang, Jixue Zhao & Yaozhong Zhang (2018) MiR-29a-5p inhibits proliferation and invasion and induces apoptosis in endometrial carcinoma via targeting TPX2, Cell Cycle, 17:10, 1268-1278, DOI: 10.1080/15384101.2018.1475829 Since publication, the authors have informed us that further experiments have not been able to replicate the findings reported in this article. As this invalidates the results and conclusions, the authors alerted the issue to the Editor and Publisher and all have agreed to retract the article to ensure the integrity of the scholarly record. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.